Early-Onset Neonatal Sepsis: Inflammatory Biomarkers and MicroRNA as Potential Diagnostic Tools in Preterm Newborns - Janec, Petr; Mojžíšek, Marek; Pánek, Martin; Haluzík, Martin; Živný, Jan; Janota, Jan (Folia biologica, 2023)
Mortality and morbidity of newborns with sepsis can be improved by early and accurate diagnosis and targeted therapy. To evaluate the early molecular events associated with inflammation and infection, we evaluated markers of endothelial activation and injury and circulating plasma miRNAs in preterm newborns with sepsis. The study group consisted of newborns with gestational age ≤ 32 weeks, with culture-positive early-onset neonatal sepsis (sepsis group, N = 8), and as a control group, we enrolled newborns without sepsis (control group, N = 12). Soluble markers of inflammation were measured using Luminex-based multiplex assay. Platelet-free plasma RNA was used to construct the library for miRNA sequencing analysis. Normalized counts were calculated and used to measure differential expression of individual detected miRNAs. We found a significant increase of interleukin 18 (IL-18) in the cord blood of the sepsis group (mean ± SEM, 104.7 ± 30.4 pg/ml vs 52.7 ± 5.6 pg/ml, P = 0.02). In peripheral blood of sepsis group patients, we found a significant increase of VEGF-A compared to controls (196.0 ± 70.5 pg/ml vs 59.6 ± 8.5 pg/ml, P = 0.02). In the cord blood plasma, eight miRNAs had significantly differential expression (P < 0.05), four miRNAs were up-regulated and four miRNAs down-regulated. In peripheral blood plasma, all nine miRNAs with significant differential expression were up-regulated. In conclusion, in early-onset neonatal sepsis, IL-18 and VEGF-A might be considered in diagnostic workup. Early-onset sepsis in preterm newborns is associated with significant changes in the circulating miRNA pattern.
Keywords: Vascular Endothelial Growth Factor A; novorozenec; Infant, Newborn; Interleukin-18; newborn; novorozenecká sepse; Infant; Humans; sepsis; kojenec; Sepsis; MicroRNAs; microRNA; Neonatal Sepsis; inflammation; interleukin-18; sepse; Inflammation; lidé; Biomarkers; zánět; endothelial biomarkers; biologické markery; vaskulární endoteliální růstový faktor A; inflammatory markers; mikro RNA